Feasibility and acceptability of theatrical and visual art to deliver fertility education to young adults. (15th March 2021) - Harper, Joyce C.; Hepburn, Jessica; Vautier, Gabby; Callander, Emma; Glasgow, Tian; Balen, Adam; Boivin, Jacky
Abstract: The Fertility Education Initiative was established in 2016 to provide education on fertility, modern families and reproductive science for young adults, teachers, health professionals, parents and adults. We report on our study to determine the feasibility and acceptability of using the arts to delivery fertility education in schools. The evaluation was mixed methods: (i) two focus groups with young people aged 14–16 and 16–18 were conducted to investigate attitudes to fertility awareness; and (ii) seventeen 16–22 year olds were divided into two groups and each undertook a day of art workshops that consisted of two visual and two theatrical workshops and then completed questionnaires at the end of each workshop and at the end of the day. The artists were interviewed using a semi-structured interview. Young adults confirmed they were interested in learning about fertility, but current understanding varied. The majority thought that fertility education should be delivered in schools at ages 16–18. During the art workshops they learnt some facts but asked for more science and discussion. They felt using art was powerful and they wanted to hear the artists personal stories. Tools using a number of platforms need to be developed that can be taken into schools nationally and evaluated for their engagement.